Use of Claim-evidence Reasoning Method in Schools to Enhance Women's Empowerment in Research - Swati A. Shinge; Seema Kiran Bandare (International Journal of Education Sciences, 2025)
In today's society, women are coming forward in all fields, their literacy rate has also increased significantly. However, just reading and writing literacy is not enough, science literacy is essential. Science literacy means understanding scientific concepts, theories and the thought process behind them and using them correctly in daily life. Unfortunately, even today, most women are found to have low science literacy. This deficiency affects their scientific outlook and limits their participation in future research and innovations. Therefore, if we want to increase women's participation in research, making science education effective at the school level is the need of the hour.The teaching method Claim-Evidence-Reasoning (CER) is very useful for this. In this method, students are asked to present a "Claim" (statement or answer) on a scientific question or problem. Then, "Evidence" (solid evidence, observations, experimental findings or statistics) is required for that statement. Finally, "Reasoning" (logical explanation) is given based on that evidence. This process teaches students to think, make observations and draw conclusions based on them instead of just memorizing facts.Claim Evidence Reasoning is an effective method of teaching, that will help the students understand the concepts of science easily, build scientific literacy among them, increase their confidence, and increase their participation in research, which will definitely help in women's empowerment. Increasing scientific literacy among women will go a long way in their overall development and empowerment. Therefore, emphasis should be placed on making science education more effective at the school level, so that women's research participation increases and society progresses. This paper has conducted a comprehensive study on how the progress of students due to teaching through the claim evidence reasoning method will contribute to women's empowerment.
Keywords: Science; Scientific Literacy; claim-evidence-reasoning; research; women empowerment